War over Kosovo : politics and strategy in a global age - Bacevich, A. J.; Cohen, Eliot A. (Columbia University Press, 2001)
While many analysts view the war for Kosovo as a one-sided affair of passing importance, this volume insists otherwise. To a greater extent than any other episode since the end of the Cold War, the war in Kosovo revealed the distinctive attributes of a new American ""way of war."" In so doing, the conflict also brought into sharp focus the dilemmas -- military, political, and moral -- confronting a liberal democracy intent on wielding preeminent power on a global scale